A counseling service for developing the qona'ah attitude of millennial generation in attaining happiness - Al Halik (Journal of Advanced Guidance and Counseling, 2020)
Purpose -  The research objective is a trial to create group counseling services with self-acceptance techniques to develop Qona’ah attitudes in realizing the happiness of the millennial generation.Method - The method used in data collection was a literature study.Result - The result of this paper is to offer group guidance and counseling using self-acceptance techniques to develop a Qona’ah attitude. Positive self-acceptance will be able to create happiness.Implications - Qona’ah attitude requires a training with strong patience, the applied counseling services  are group guidance and counseling services with four stages.Originality - A method of developing the Qona’ah attitude of the millennial generation is a process of providing professional assistance which is characterized by a continuous process with systematic steps to an individu or groups of people. Tujuan -  Tujuan penelitian ini adalah uji coba untuk menciptakan layanan konseling kelompok dengan teknik penerimaan diri untuk mengembangkan sikap Qona’ah dalam mewujudkan kebahagiaan generasi milenial.Metode - Metode yang digunakan adalah studi pustaka.Hasil - Hasil dari penelitian ini adalah menawarkan bimbingan dan konseling kelompok menggunakan teknik penerimaan diri untuk mengembangkan sikap Qona’ah. Penerimaan diri yang positif akan mampu menciptakan kebahagiaan.Implikasi - Sikap Qona’ah membutuhkan pelatihan dengan kesabaran yang kuat, layanan konseling yang diterapkan adalah layanan bimbingan dan konseling kelompok dengan empat tahap.Orisinalitas - Metode pengembangan sikap Qona’ah generasi milenial melalui proses pemberian bantuan profesional yang bercirikan proses berkelanjutan dengan langkah-langkah sistematis kepada individu atau kelompok masyarakat.